1. MODEL OF CONGENITAL HEART DEFECTS AT CHILDREN'S HOSPITAL 2 IN 2024 (Vietnam Journal of Community Medicine, 2025)
Objective: Survey of congenital heart defect models at the Cardiology Department of Children's Hospital 2, Ho Chi Minh City in 2024.Methods: Cross-sectional descriptive study with subjects being all children with congenital heart defects admitted to the Cardiology Department, Children's Hospital 2, Ho Chi Minh City, in 2024. Information on epidemiology, diagnosis, and treatment outcomes of the study subjects was collected and statistically analyzed.Results: A total of 716 patients were included in the study, with an average age of 31.5 months (±40.8). The highest proportion of patients (27.2%) was in the 1–6 month age group. Among these pediatric patients, 65.2% came from provincial areas. Prenatal diagnosis was reported in 4.4% of cases. Malnutrition was prevalent, affecting 78.49% of the children. Within this group, 40.78% were classified as underweight, 19.69% as stunted, and 18.02% as emaciated. Genetic syndromes were the most common associated condition, present in 3.6% of the cases. In terms of congenital heart defects (CHD), left-to-right shunt defects accounted for 59% of cases, followed by cyanotic CHD at 31%. The three most common types of defects were ventricular septal defect (25.1%), patent ductus arteriosus (16.7%), and tetralogy of Fallot (12.8%). Definitive treatment was performed in 54.8% of the patients, including 34% who underwent surgery and 20.8% who received catheter-based interventions. After treatment, 73.3% of the children showed improvement, and 15% achieved complete recovery. The overall mortality rate was 2.5%, with severe infections being the primary cause, accounting for 72.7% of the deaths. The median postoperative hospital stay was 4 days, and 63% of patients were discharged within 14 days of surgery.Conclusion: CHD includes many heart defects, from simple to complex, and currently, Children's Hospital 2 has applied many methods in treatment and had more positive results than before
Keywords: Congenital Heart disease, pediatric disease, Children’s Hospital 2.